A CASE REPORT: HYPERTENSION IN PREGNANCY - Kristiyani, Sagung Desy (E-Jurnal Medika Udayana, 2014)
Hypertension in pregnancy is 15 percent of the comorbid of pregnancy and one of the three highest causes of maternal mortality and morbidity in childbirth. This can be either Chronic Hypertension, Gestational Hypertension,and developed further into Preeclampsia or Eclampsia. In Indonesia, the mortality and morbidity of hypertension in pregnancy is also still quite high. This is caused not only by the etiology that is stillunclear, but also by childbirth care that is still handled by non-medical officers and referral system which has not been perfect. This case report discusses about Severe Preeclampsia with Impending Eclampsiaon a 28 years old pregnant woman, supporting urinalysis examination showed protein and ketones in the urine, blood chemistry examination also obtained an increase of the liver enzyme and lactate dehydrogenase . In these patients is done handling a termination of pregnancy by Sectio Caesarea method.
Keywords: Hypertension, Pregnancy, Hypertension in pregnancy